Evaluation of novel rapid detection kits for dengue virus NS1 antigen in Dhaka, Bangladesh, in 2017 - Keita Suzuki (Virology Journal, 2019)
Abstract Background Dengue virus (DENV) infection is one of the biggest challenges for human health in the world. In addition, a secondary DENV infection sometimes causes dengue hemorrhagic fever (DHF), which frequently leads to death. For this reason, accurate diagnosis record management is useful for prediction of DHF. Therefore, the demand for DENV rapid diagnosis tests (RDTs) is increasing because these tests are easy and rapid to use. However, commercially available RDTs often show low sensitivity for DENV and cross-reactivity against other flaviviruses, especially Zika virus (ZIKV). Methods We developed two types of novel DENV non-structural protein 1 (NS1) detection RDTs, designated TKK-1st and TKK-2nd kits. Specificities of the monoclonal antibodies (MAbs) used in these kits were confirmed by enzyme-linked immuno-sorbent assay (ELISA), dot blot, and western blot using recombinant NS1 proteins and synthetic peptides. For evaluation of sensitivity, specificity, and cross-reactivity of the novel DENV NS1 RDTs, we first used cultured DENV and other flaviviruses, ZIKV and Japanese encephalitis virus (JEV). We then used clinical specimens obtained in Bangladesh in 2017 for further evaluation of kit sensitivity and specificity in comparison with commercially available RDTs. In addition, RNA extracted from sera were used for viral genome sequencing and genotyping. Results Epitopes of three out of four MAbs used in the two novel RDTs were located in amino acid positions 100 to 122 in the NS1 protein, a region that shows low levels of homology with other flaviviruses. Our new kits showed high levels of sensitivity against various serotypes and genotypes of DENV and exhibited high levels of specificity without cross-reactivity against ZIKV and JEV. In clinical specimens, our RDTs showed sensitivities of 96.0% (145/151, TKK-1st kit) and 96.7% (146/151, TKK-2nd kit), and specificities of 98.0% (98/100, TKK-1st kit and TKK-2nd kit). On the other hand, in the case of the commercially available SD Bioline RDT, sensitivity was 83.4% (126/151) and specificity was 99.0% (99/100) against the same clinical specimens. Conclusions Our novel DENV NS1-targeting RDTs demonstrated high levels of sensitivity and lacked cross-reactivity against ZIKV and JEV compared with commercially available RDTs.